Efeitos do jogo Abrakedabra sobre a leitura e a escrita de palavras com encontros consonantais - Miyuki Suzuki, Beatriz; Regina de Souza, Silvia (Acta Comportamentalia, 2019)
Reading and writing are important behaviors in people’s lives, highlighting the importance of the development of educational technology. Several studies point that educational games can be effective to teach reading and writing because of its motivational character and the possibility of programming them according to Behavior Analysis principles. The current study aims to evaluate the prototype of the educational game Abrakedabra, Version 2, in teaching words with consonantal encounters and in the usability and engagement. The game Abrakedabra was modified to include words with consonantal clusters and the prototype of the modified game was evaluated. One 5-year-old child who did not read or write words with consonantal clusters participated. The experimental stimuli used in the study was spoken words (A), words spoken by the child (A’), printed words (B), figures (C), handwritten words (D) and set of letters (E), oral spelling (F), spoken syllable (G) and printed syllable (H).In the pre-test, the relations CD, CB, BA’ and AE were evaluated. In the intervention, the MTS and CRMTS procedures were used to teach, through the game Abrakedabra, the relations between BA’, AA’, HÁ’, BE, AE, HE, GH, AC, BC, BD, AD, AF and BF. The post-test was similar in structure to the pretest. There was an increase in the number of words correctly read (BA’) and letters correctly selected (AE). Regarding the syllables with consonantal clusters, the increase of words correctly read was only for the taught words, but not in recombinative reading. The results suggest that the game can be used to teach words with consonantal clusters, however, there is a need to readjust it and changes in the teaching procedure.